MiR-144 suppresses proliferation, invasion, and migration of breast cancer cells through inhibiting CEP55 - Yin, Yuanqin (Cancer Biol Ther, 2018)
Objective: The study aimed to investigate the molecular mechanism of miR-144 and CEP55 as well as the influence of their interaction on the cell proliferation, migration, invasion, cell cycle and cell apoptosis in breast cancer. Methods: In this study, The Cancer Genome Atlas (TCGA, https://tcga-data.nci.nih.gov/) database was used for microarray analysis. The expressions of miR-144 and CEP55 in 40 adjacent tissues and 36 tumor tissues were examined by western blot, qRT-PCR and immunohistochemistry. The target relationship between miR-144 and CEP55 was predicted and confirmed by TargetScan and luciferase reporter assay. The cell proliferation, cell cycle and cell apoptosis in different groups were detected by MTT and flow cytometry assays, while wound healing and transwell assays were used for the cell migration and invasion tests. The regulatory effects of miR-144 and CEP55 on breast tumor were verified through nude mouse model in vivo experiment. Results: MiR-144 was down-regulated in breast cancerous tissues and cells, whereas CEP55 expression was up-regulated in breast cancerous tissues. Moreover, there existed a target relationship between miR-144 and CEP55 and negative correlation on their expressions. MiR-144 could down-regulate CEP55 expression, thereby inhibiting proliferation, invasion, migration, retarding cell cycle and accelerating cell apoptosis. MiR-144 could inhibit cell progression through down-regulating CEP55 in vivo. Conclusion: MiR-144 suppressed cell proliferation, migration, invasion and induced cell cycle arrest and cell apoptosis by repressing CEP55. This might provide a promising therapy for clinical treatment.